Patient perspectives on pain care pathways: informing implementation with insights from trial evidence - Lindsay A. Ballengee; Susan N. Hastings; Trevor A. Lentz; Katlin Harker; Steven Z. George (Frontiers in Public Health, 2026)
Background Few studies have examined whether patients' perceptions of low back pain (LBP) care pathways are influenced by evidence of their effectiveness. To inform future implementation efforts, we conducted an exploratory qualitative study examining how individuals with low back pain interpreted two pain care pathways that emphasized non-drug treatment options: a physical therapy–focused model (Sequenced Care Pathway) and a navigator-led model (Pain Navigator Pathway). We explored how individuals with low back pain perceived the acceptability, feasibility, value, and fit of these approaches before and after reviewing comparative effectiveness trial results. Methods Guided by the Theoretical Domains Framework, we conducted a qualitative study of individuals living with LBP using five small-group discussions and follow-up individual interviews with the same participants ( n = 10). Participants were recruited from a patient and family advisory council at an academic medical center. Discussions explored perceptions of both pathways before and after participants reviewed trial results which indicated no pathway superiority for pain and functional outcomes. Findings Participants viewed both pathways as acceptable; however, their interpretations and preferences were shaped primarily by prior experiences, access to care, perceived fit, and logistical considerations rather than trial results. Trial findings were typically interpreted as reinforcing existing preferences. The Pain Navigator Pathway was valued for coordination, support, and system navigation, while the Sequenced Care Pathway was viewed as structured and appropriate for specific patient contexts. Conclusions In this exploratory qualitative study, participants' preferences were shaped by perceived fit, prior experiences, and healthcare system context, and remained largely stable after exposure to trial results showing no pathway superiority. These findings suggest that incorporating patient perspectives may help inform the design and implementation of pathway-based care, particularly in the commonly occurring instance when comparative effectiveness results do not identify a clearly superior approach.